Feeding a Membrane-less Microbial Fuel Cell by Mixed Municipal and Industrial Wastewater - Włodarczyk, Barbara; Włodarczyk, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Due to the constant growth of the world`s population, the amount of generated wastewater is also constantly increasing. One of the devices that can use wastewater as a raw material for energy production is a microbial fuel cell (MFC). MFCs technology is constantly evolving. However, to increase its use, it is necessary to improve its efficiency. There are various possibilities to ensure this, such as the use of new electrode materials, new cell designs, or the use of wastewaters from different sources.
Keywords: bioelectricity; bioenergy; microbial fuel cell; yeast process wastewater; environmental engineering; renewable energy sources; wastewater treatment; COD reduction; environmental protection